174k views
3 votes
(-1/8c+16)-(3/8+3c)=

User Roboles
by
6.0k points

1 Answer

6 votes

Final answer:

To solve the expression (-1/8c+16)-(3/8+3c), distribute the negative sign and combine like terms to simplify the expression. The final answer is 16c+257/8.

Step-by-step explanation:

To solve the expression (-1/8c+16)-(3/8+3c), we can simplify the expression by distributing the negative sign. First, distribute the negative sign to (-3/8-3c):

(-1/8c+16)-(-3/8-3c)

Next, combine like terms and simplify:

=(-1/8c+16)+3/8+3c)

=(-1/8c+3c)+(16+3/8)

= (2c-1/8c)+(129/8)

=(16c+2)+(129/8)

=16c+2+129/8

=16c+257/8

User Vipin
by
7.0k points